Karakterisasi Polutan Logam dan Potensi Radioaktif dalam E-Liquid Rokok Elektrik - Huboyo, Haryono Setiyo; Naristiana Putra, Alif Aziz; Bimastyaji Surya Ramadhan; Ika Bagus Priyambodo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Electronic cigarettes have become a popular alternative for smokers, but research on the pollutants contained in these products remains limited, especially in Indonesia. This study aims to characterise the metal content and radioactive potential of e-liquid from electronic cigarettes marketed in Indonesia. Five e-liquid samples from popular brands were selected based on user surveys and analysed to detect potential hazards. The samples consisted of mango-flavoured saline nicotine e-liquid with a nicotine concentration of 30 mg, which was analysed using neutron activation analysis (NAA) and total alpha and beta radiation measurements. The results showed the presence of heavy metals such as aluminium (Al), titanium (Ti), copper (Cu), nickel (Ni), arsenic (As) and manganese (Mn) with varying concentrations between samples. Aluminium was the dominant metal with the highest concentration reaching 66.256 ± 6.131 µg/g. Although alpha and beta radiation activity was below the detection limit, the presence of certain heavy metals, such as nickel and arsenic, indicates potential health and environmental risks. This study provides valuable insights into the contaminants in e-liquid products in Indonesia, which can be used as a basis for developing regulations to improve product safety.